Influence of sodium hypochlorite on STEC biofilm formation - Velez, Maria Victoria (2019)
Shiga toxin-producing Escherichia coli (STEC) include several serotypes isolated fromcases of hemorrhagic colitis and hemolytic uremic syndrome. Bacteria form biofilmsin different environments, which can contaminate food and generate infections, whileprotecting themselves against adverse conditions such as the use of disinfectants. The aimof this study was to evaluate the effects of sodium hypochlorite at different concentrationsand exposure times on the formation of STEC biofilms. In vitro assays on polystyrene plateswere performed and the strains were classified according to their ability to form biofilm.They were exposed to different solutions of NaClO. The results showed that biofilmformation was moderate or weak in most cases and the use of hypochlorite is effective atconcentrations greater than or equal to 5% for at less 20min.